2017
DOI: 10.1002/hipo.22732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of M1 and M4 activation on excitatory synaptic transmission in CA1

Abstract: Hippocampal networks are particularly susceptible to dysfunction in many neurodegenerative diseases and neuropsychiatric disorders including Alzheimer's disease, Lewy body dementia, and schizophrenia. CA1, a major output region of the hippocampus, receives glutamatergic input from both hippocampal CA3 and entorhinal cortex, via the Schaffer collateral (SC) and temporoammonic (TA) pathways, respectively. SC and TA inputs to CA1 are thought to be differentially involved in the retrieval of previously stored memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 102 publications
(197 reference statements)
6
44
1
Order By: Relevance
“…We further extended previous studies by demonstrating that suppression of SLM inputs by ACh release was mediated by muscarinic M2 receptor activation. These latter findings were consistent with observations from a recent study that suggest that presynaptic inhibition at synapses in the SLM was not mediated by M4 muscarinic receptors (Thorn et al 2017). Therefore, our data confirms and extends observation made by previous studies and suggest that ACh release from MS/DBB cholinergic terminals results in presynaptic inhibition of inputs in the SLM via the activation of M2 receptors.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We further extended previous studies by demonstrating that suppression of SLM inputs by ACh release was mediated by muscarinic M2 receptor activation. These latter findings were consistent with observations from a recent study that suggest that presynaptic inhibition at synapses in the SLM was not mediated by M4 muscarinic receptors (Thorn et al 2017). Therefore, our data confirms and extends observation made by previous studies and suggest that ACh release from MS/DBB cholinergic terminals results in presynaptic inhibition of inputs in the SLM via the activation of M2 receptors.…”
Section: Discussionsupporting
confidence: 94%
“…Our studies extended these studies by being the first to investigate modulation of synaptically released ACh on excitatory afferents in SLM. Consistent with studies utilizing bath application of cholinergic agonists, we observed that ACh release suppressed excitatory inputs in SLM (M. Hasselmo and Schnell 1994;Thorn et al 2017). Furthermore, ACh release appeared to act presynaptically as the inhibition of afferents in SLM was accompanied by an increase in the PPR, which is frequently used to determine presynaptic function.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Perhaps counter-intuitively, acetylcholine inhibits both TA and SC glutamatergic excitatory transmission in CA1. In the SC pathway this occurs via presynaptic muscarinic M 4 receptors but the identity of the receptors mediating depression at the TA pathway is unclear (Dasari and Gulledge, 2011; Goswamee and McQuiston, 2019; Thorn et al, 2017). The anatomically segregated targeting of TA and SC inputs to distal and more proximal dendritic locations on…”
Section: Introductionmentioning
confidence: 99%